The properties and regulation of functional acetylcholine receptors on chick ciliary ganglion neurons - Margiotta, JF (J Neurosci, 1987)
The properties of acetylcholine receptor (AChR) channels on chick ciliary ganglion neurons in culture were examined using patch-clamp recording techniques. Acetylcholine (ACh) was applied by rapid microperfusion. Whole-cell current noise analysis revealed a single class of functional receptors on the neurons. Dose-response studies indicated a Kd of about 36 microM and a Hill coefficient of 1.5–1.7, predicting 2 ACh binding sites per receptor. Both fast and slow components of receptor desensitization were observed. Single-channel recordings from excised outside-out patches of soma membrane exposed to 2–5 microM ACh indicated a single-channel conductance of 40 pS, a reversal potential of -9 mV, a mean open duration of 1 msec, and an opening probability of 0.34. The kinetic behavior of the channels was provisionally described by a 3-closed, 1-open state model for receptor activation. In all of these properties, AChRs of ciliary ganglion neurons resemble those on skeletal muscle fibers. Growing the neurons in an elevated K+ concentration produced a 2–3-fold decrease in peak whole-cell currents induced by ACh under standard test conditions, without altering any of the single-channel properties described above. Neither changes in cholinesterase activity nor receptor distribution accounted for the decrease. Instead, calculations indicated that elevated K+ reduced the ACh response by decreasing the number of functional AChRs on the neurons. No K+-dependent decrease is observed, however, in the number of total receptors on the neurons detected either by a monoclonal antibody specific for the receptor or by an alpha-neurotoxin that binds to the receptor and blocks its function. Moreover, the number of receptors detected by the 2 probes is at least 10-fold greater than the calculated number of functional receptors. The findings suggest that only a small fraction of the AChRs on the neuronal surface is functional and that the cell can alter the ratio of functional and nonfunctional receptors in response to growth conditions.